1
$\begingroup$

so im supposed to rewrite $P\lor Q$, and , $P \Rightarrow Q , P \Leftrightarrow Q$ in terms of $\lnot$ and $\land$

this is what i got

$P \lor Q = ¬ P \land ¬ Q$

$P \land Q = P~Q$ (same thing?)

$P ⇒ Q = Q \lor ¬P$

$P ⇔ Q = ¬ P \land ¬Q$

those loook right?

$\endgroup$
0
$\begingroup$

The first three are right, the fourth should be: $$P \iff Q \equiv (P \land Q) \lor (\lnot P \land \lnot Q) \equiv \lnot (\lnot (P \land Q) \land \lnot (\lnot P \land \lnot Q))$$

$\endgroup$
-1
$\begingroup$
  1. almost correct, it is just the opposite
  2. yes, the same thing ($P\land Q$)
  3. go further, use 1. to express it by $\land,\ \lnot$
  4. not correct. use 3. and $P\Leftrightarrow Q = (P\Rightarrow Q)\land(Q\Rightarrow P)$
    (and probably simplify if possible)
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.